Petuah Ali Haji (1809-1872) Tinjauaan tentang Thamrah al-Muhimmah - Syamsul Anwar (Al-Jami'ah: Journal of Islamic Studies, 1998)
Ali Haji (b. 1809) was as a prolific writer and considered to be a Malay historian of the nineteenth century Riau-Lingga. He produced many literary works, some of which have been translated into Dutch and English as well. However, his works on religions are remained untouched by European translators. One of his major works, Thamrah al-Muhimmah shows the great extent to which he mastered Islamic sciences, particularly Islamic law. It proves the position of AIi Haji as a religious scholar in contemporary Malay. The current paper is devoted to explore the significance of Thamrah al-Muhimmah. The author discovers two important points of the Thamrah al-Muhimmah: The position of religion in the context of Malay political life in the nineteenth century Riau-Lingga Kingdom, and the renewal of the traditional Malay political literature.